Energy and Sustainable Futures: Proceedings of the 3rd ICESF, 2022 - Nixon, Jonathan D.; Al-Habaibeh, Amin; Vukovic, Vladimir; Asthana, Abhishek (Springer Proceedings in Energy, 2023)
This is an open access book. This book contains research papers presented at the 3rd International Conference on Energy and Sustainable Futures (ICESF), which took place at Coventry University, UK, in 2022. The ICESF is an annual conference organised by the UK-based Doctorial Training Alliance (DTA) programme. It is a multidisciplinary conference focused on addressing the future challenges and opportunities for meeting global energy targets and sustainable development goals. The conference brought together academic researchers, industry experts and research students to showcase the latest innovations and research on a wide range of topics in the areas of energy and sustainability, including • renewable energy; • ICT and control; • computational fluid dynamics; • optimization; • conventional energy sources; • energy governance; • materials in energy research; • energy storage and • energy access.